A single session of testing for one repetition maximum (1RM) with eight exercises is trustworthy - Neto, José Campanholi [UNESP]; Cedin, Luísa; Dato, Carla Cristina [UNESP]; Bertucci, Danilo Rodrigues [UNESP]; Perez, Sérgio Eduardo de Andrade; Baldissera, Vilmar [UNESP] (My University, 2015)
Campanholi Neto J, Cedin L, Dato CC, Bertucci DR, Perez SEA, Baldissera V. A Single Session of Testing for One Repetition Maximum (1RM) with Eight Exercises is Trustworthy. JEPonline 2015;18(3):74-80. Although the 1RM test is used as the gold standard for assessing muscle strength in non-laboratory situations, the question is this: Are the 1RM values performed in a single exercise session with 8 exercises trustworthy? Sixteen male subjects (mean ± SEM: age 27.3 ± 1.0 yrs; height, 179.1 ± 1.8 cm; body mass, 89.3 ± 2.9 kg; body mass index 27.8 ± 0.6 kg·m-2; and fat percentage 18.7 ± 1.5%) participated in this study. They completed two 1RM test sessions with 8 exercises. Session one (T-1RM): leg press, bench press, squat, front pulldown, leg curl machine, pushdown on a cable machine, leg extension machine, biceps barbell curl. Session two (RT-1RM) inverse order of the exercises was used, starting with the weight of 1RM found on the first test (T-1RM). Six blood samples were collected to analyze blood lactate concentration. The results of this study demonstrated the reliability of 1RM test in a single session with 8 exercises. A high intraclass correlation coefficient was also found (ranging from 0.911 to 0.993). The findings indicate that a single 1RM test session with 8 exercises is a reliable test without the need for a second session to confirm the previous values.
Keywords: Lactic acid; Resistance training; Training intensity